PEDAGOGICAL COMPETENCE AND LINGUISTICS: AN INTEGRATED APPROACH - Shoxista Asqarovna Zoitova (International Journal of Literature and Language Studies, 2026)
Abstract This article analyzes the role of pedagogical competence in the modern education system, its components, factors influencing its formation, and its significance. Pedagogical competence is considered as a combination of knowledge, skills, abilities, and personal qualities necessary for the effective implementation of a teacher’s professional activities. Particular attention is paid to the relationship between pedagogical competence and linguistics in language teaching. The article also reveals the main types of pedagogical competence and suggests ways of developing them.